Selective Sweeps Lead to Evolutionary Success in an Amazonian Hyperdominant Palm - Melo, Warita A.; Vieira, Lucas D.; Novaes, Evandro; Bacon, Christine D.; Collevatti, Rosane G. (Frontiers in Genetics, 2020)
Despite the global importance of tropical ecosystems, few studies have identified how natural selection has shaped their megadiversity. Here, we test for the role of adaptation in the evolutionary success of the widespread, highly abundant Neotropical palm Mauritia flexuosa. We used a genome scan framework, sampling 16,262 SNPs with target sequence capture in 264 individuals from 22 populations in rainforest and savanna ecosystems. We identified outlier loci as well as signal of adaptation using Bayesian correlations of allele frequency with environmental variables and detected both selective sweeps and genetic hitchhiking events. Functional annotation of SNPs with selection footprints identified loci affecting genes related to adaptation to environmental stress, plant development and primary metabolic processes. The strong differences in climatic and soil variables between ecosystems matched the high differentiation and low admixture in population Bayesian clustering. Further, we found only small differences in allele frequency distribution in loci putatively under selection among widespread populations from different ecosystems, with fixation of a single allele in most populations. Taken together, our results indicate that adaptive selective sweeps related to environmental stress shaped the spatial pattern of genetic diversity in M. flexuosa, leading to high similarity in allele frequency among populations from different ecosystems.